A Linguistic Analysis of Disadvantaged Kindergarten Children's Verbal Responses to Questions. - Simmons, Barbara (Journal of Educational Research, 1976)
The purpose of this study was to analyze the verbal responses of 72 disadvantaged kindergarten pupils to data recall, data processing, or application questions. Results for each sex and scores for each category of questions on the variables of total word count, vocabulary diversity, and mean length of T-unit were compared utilizing the multiple classification analysis of covariance technique and Duncan’s New Multiple Range Test. Data processing and application questions resulted in a statistically significant increase (.01) in total word count A significant increase (.01) in mean length of T-unit was recorded when subjects responded to data processing or application questions. The type of question which was utilized resulted in a significant difference (.05) in the children’s vocabulary diversity scores.